2023
DOI: 10.1038/s41598-023-28364-y
|View full text |Cite
|
Sign up to set email alerts
|

Ignition of the southern Atlantic seafloor spreading machine without hot-mantle booster

Abstract: The source of massive magma production at volcanic rifted margins remains strongly disputed since the first observations of thick lava piles in the 1980s. However, volumes of extruded and intruded melt products within rifted continental crust are still not accurately resolved using geophysical methods. Here we investigate the magma budget alongside the South Atlantic margins, at the onset of seafloor spreading, using high-quality seismic reflection profiles to accurately estimate the oceanic crustal thickness.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 58 publications
(99 reference statements)
0
6
0
Order By: Relevance
“…After crustal breakup, variations in oceanic crust thickness in the study area fall within the standard range (4-8 km) (Graça et al, 2019;Sauter et al, 2023) (Figure 4). This suggests the absence of a regional upper-mantle thermal anomaly at the time of crustal breakup.…”
Section: Implications For the Central South Atlanticmentioning
confidence: 64%
“…After crustal breakup, variations in oceanic crust thickness in the study area fall within the standard range (4-8 km) (Graça et al, 2019;Sauter et al, 2023) (Figure 4). This suggests the absence of a regional upper-mantle thermal anomaly at the time of crustal breakup.…”
Section: Implications For the Central South Atlanticmentioning
confidence: 64%
“…contrast, on land to the north, the distribution of Serra Geral coincides with that of the Palaeozoic Parana Basin. As discussed in Sauter et al (2023), this observed rapid decrease in magmatic volumes along strike may suggest that the large magmatic volumes observed in the north of the Pelotas margin (e.g., Torres High) are generated by a component of mantle inheritance rather than the usually assumed mantle-plume mechanism alone.…”
Section: Along Strike Variation Of Magmatic Addition Along the Pelota...mentioning
confidence: 86%
“…with breakup evolution being controlled by the Tristan mantle plume resulting in the Paraná-Etendeka magmatic province (Thompson et al, 2001;Peace et al 2020). In contrast, a more recent study by Sauter et al (2023) shows that the magmatic budget along large parts of the Austral segment does not need a hot-mantle booster and that higher magmatic budgets can only be observed north of the Chui-Cape Cross Fracture Zone when approaching the Paraná-Etendeka magmatic province. Sauter et al (2023) analysed, however, only the magmatic budget recorded in the first oceanic crust.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…Magma‐rich margins are sometimes associated with mantle plumes, which can produce advanced decompression melting with respect to crustal thinning due to higher asthenosphere temperature or increased water content. However, the observation of magma‐rich margins with thick SDRs and magmatic intrusion/underplate immediately followed by the first oceanic crust thinner than normal (e.g., Uruguay, N‐Argentina, Guyana; Sauter et al., 2023; Trude et al., 2022) implies that mantle plumes are not the only and/or most common cause of magma‐rich margins.…”
Section: Discussionmentioning
confidence: 99%